2021
DOI: 10.3390/cancers13061245
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor MTUS1/ATIP1 Modulates Tumor Promotion in Glioma: Association with Epigenetics and DNA Repair

Abstract: Glioblastoma (GBM) is a highly aggressive brain tumor. Resistance mechanisms in GBM present an array of challenges to understand its biology and to develop novel therapeutic strategies. We investigated the role of a TSG, MTUS1/ATIP1 in glioma. Glioma specimen, cells and low passage GBM sphere cultures (GSC) were analyzed for MTUS1/ATIP1 expression at the RNA and protein level. Methylation analyses were done by bisulfite sequencing (BSS). The consequence of chemotherapy and irradiation on ATIP1 expression and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…MTUS1 expression is downregulated in several types of malignancies, such as breast cancer 37 , colorectal carcinoma 38 and gastric cancer 39 . ATIP1, which is one of the major products of the MTUS1 gene, plays a pivotal role in the carcinogenesis of several malignancies 40 . Our previous study verified that HNSCC cells showed notably reduced ATIP1 expression 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…MTUS1 expression is downregulated in several types of malignancies, such as breast cancer 37 , colorectal carcinoma 38 and gastric cancer 39 . ATIP1, which is one of the major products of the MTUS1 gene, plays a pivotal role in the carcinogenesis of several malignancies 40 . Our previous study verified that HNSCC cells showed notably reduced ATIP1 expression 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ATIP3, ATIP1 also plays a role in tumor progression. Overexpression of ATIP1 interferes with tumor irradiation, therapy by increasing DNA damage repair in glioblastoma [30] . Our studies revealed that ATIP1 is responsible for PC3-cell-directed migration and invasion across Matrigel-coated inserts.…”
Section: Discussionmentioning
confidence: 99%
“… [30] found that ATIP1 expression was downregulated in malignant glioma, probably due to promoter hypermethylation. Furthermore, high ATIP1 expression might retard the response to radiation therapy by enhancing double-strand DNA break repair [30] . ATIP1 participates in p53-involved tumor signal transduction through binding between the ATIP1 promoter and p53 [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Promoter hypermethylation is identified to play an important role during tumorigenesis through silencing the gene expression of tumor suppressor genes [ 33 , 34 ]. Based on a genome-wide screening performed by Li Y et al, aberrant hypermethylation of α-internexin gene promoter was identified in both colon adenoma and cancer, and the findings were validated in biospecimens of 30 normal colons, 37 adenomas, and 30 colon cancers using quantitative methylation-specific PCR, and the silenced α-internexin expression by epigenetic alteration was confirmed in CRC cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%